Predictors of Breastfeeding Success in Postpartum Period: Delivery Type, Postpartum Support, and Postpartum Depression - Kiliçli, Ayşegül; Gül, Sidar (Ataturk Universitesi, 2024)
Objective: This study aimed to investigate the association between delivery type, postpartum support need and postpartum depression on breastfeeding success in the first postpartum month. Methods: This study, conducted between August 8, 2022 and August 31, 2023, was comparative, prospective and cross‐sectional. Sample consisted of 300 women (150 vaginal, 150 cesarean section). Data were collected using Descriptive Information Form, Postpartum Support Questionnaire, Edinburgh Postpartum Depression Scale, and Bristol Breastfeeding Assessment Tool. Multiple linear regression was used to identify the predictors of breastfeeding success. Results: Those who did not received sufficient support rate was 50.7%, the presence of postpartum depression was 54.0%, and the mean breastfeeding success score was 6.4±0.9 which was moderate. Cesarean delivery (β=‐0.149, p<.01), increased need for postpartum support (β=‐0.203, p<.01) and postpartum depression (β=0.261, p<.01) were significant predictors which were explaining 21.0% of total variance in breastfeeding success. The breastfeeding success of cesarean section mothers who did not have postpartum depression but received inadequate support decreased by 20.3% compared to vaginal birth mothers. Mothers who gave birth by caesarean section, did not receive postpartum support and were at risk of postpartum depression had the lowest breastfeeding success. Conclusion: Cesarean section, postpartum support, and postpartum depression are factors that significantly affect breastfeeding success. Therefore, breastfeeding counselling services for mothers in the postpartum care process should be planned and implemented individually to address mode of delivery, need for postpartum support and postpartum depression. © 2024, Ataturk Universitesi. All rights reserved.
Postpartum Dönemde Emzıṙme Başarısının Belıṙleyıċı̇lerı̇: Doğum Şekli, Postpartum Destek ve Postpartum Depresyon
Keywords: Birth type; depression; lactation; postpartum; support